Identification of the structural features that mediate binding specificity in the recognition of STAT proteins by dual-specificity phosphatases - Jardin, Christophe; Sticht, Heinrich (Journal of Biomolecular Structure & Dynamics, 2012)
Inactivation of signal transducers and activators of transcription (STAT) proteins is regulated by dual-specificity phosphatases (DSPs) with high substrate specificity. Although experiments have provided useful information about the phosphatase activity and the specificity for STATs, there is up-to-date no data at a molecular level to explain the specific recognition of STAT substrates by this subfamily of phosphatases. Here, a combined approach of molecular modeling, docking and molecular dynamics simulations was used to address the binding between DSPs and their STAT substrates. We identified a binding interface at the protein tyrosine phosphatase (PTP) domain of the DSP VHR that interacts with the SH2-domain of STAT5. This finding is consistent with previous mutational data and supports a "two-step" mechanism for the dephosphorylation event. Application of the same approach suggests the presence of a similar interface between the viral DSP VH1 and STAT1. Furthermore, the interaction network at this interface provides an explanation for the specificity of the DSP-STAT recognition.
EVALuna2:26258